Errores probatorios en materia tributaria - Dávila Alvarado, César Alejandro (2023)
The aims of this paper are: (i) at a conceptual level, to present a typology (not exhaustive) of evidentiary errors that usually occur in tax proceedings and processes in Peru, grouped according to the stages of the evidentiary activity where they occur, and to propose a terminological apparatus to describe with greater explanatory power what happens when a decision is made on the factual premise in tax proceedings and processes. Similarly, (ii) with regards to the dogmatic dimension, an examination shall be undertaken to scrutinize the legal ramifications ensuing from these errors, in strict accordance with the prevailing legal framework.